2010
DOI: 10.4049/jimmunol.1000261
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide RNA Interference inDrosophilaCells Identifies G Protein-Coupled Receptor Kinase 2 as a Conserved Regulator of NF-κB Signaling

Abstract: Because NF-κB signaling pathways are highly conserved in evolution, the fruit fly Drosophila melanogaster provides a good model to study these cascades. We carried out an RNA interference (RNAi)-based genome-wide in vitro reporter assay screen in Drosophila for components of NF-κB pathways. We analyzed 16,025 dsRNA-treatments and identified 10 novel NF-κB regulators. Of these, nine dsRNA-treatments affect primarily the Toll pathway. G protein-coupled receptor kinase (Gprk)2, CG15737/Toll pathway activation med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 49 publications
4
85
1
Order By: Relevance
“…We further demonstrated that the il-1b-myd88 axis and NADPH oxidase-mediated ROS pathway are differentially required for basal random movement and injury-induced directional migration of neutrophils. Although MO knockdown is a transient and incomplete inactivation of the targeted genes and has a nonspecific toxic effect (55), the MOs used in this study are highly specific and have minimal toxic effect, as well documented by others (23,(28)(29)(30) and ourselves. We believe that the phenotypes we have observed in our study will likely represent the loss-of-function of the targeted genes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We further demonstrated that the il-1b-myd88 axis and NADPH oxidase-mediated ROS pathway are differentially required for basal random movement and injury-induced directional migration of neutrophils. Although MO knockdown is a transient and incomplete inactivation of the targeted genes and has a nonspecific toxic effect (55), the MOs used in this study are highly specific and have minimal toxic effect, as well documented by others (23,(28)(29)(30) and ourselves. We believe that the phenotypes we have observed in our study will likely represent the loss-of-function of the targeted genes.…”
Section: Discussionmentioning
confidence: 89%
“…We speculated that a similar mechanism might be used in zebrafish. To test this hypothesis, two MOs, myd88atg and myd88e2i2, which interfere with myd88 mRNA translation and splicing, respectively (28,29), were coinjected to effectively knock down myd88 expression in zebrafish embryos followed by tail fin amputation and bacterial injection (Supplemental Fig. 2G).…”
Section: Tissue Injury Activates Il-1b Signalingmentioning
confidence: 99%
“…Genome-wide RNA interference in Drosophila identified G protein-coupled receptor kinase (Gprk)2, which in other organisms is homologous to GRK5, to be a conserved regulator of NF〉 (255). Further studies have also confirmed GRK5 as a mediator of NF〉 signaling in mammals, with potential implications in cardiac hypertrophy and other cardiovascular pathologies, although the mechanism of action is still not fully understood (114,170,232).…”
Section: A Grk5 and Its Role In Pathological Cardiac Hypertrophy Andmentioning
confidence: 99%
“…For example, the ubiquitination state of various pathway components is delicately regulated. The E3-ligase Iap2 has been identified in many large-scale screens for Imd pathway regulators (60,66,69,70), and it also was shown to be essential for Imd pathway-mediated AMP expression and bacterial resistance in vivo (60,65,71). In addition, a number of ubiquitinating and deubiquitinating enzymes have been implicated in the negative regulation of the signaling pathway.…”
Section: Regulation Of the Imd Signaling Pathwaymentioning
confidence: 99%